TOPSIS and fuzzy multi-objective model integration for supplier selection problem - Jadidi, Omid; Tang, Sai Hong; Firouzi, Fatemeh; Mohd Yusuff, Rosnah; Zulkifli, Norzima (2008)
Purpose: The problem includes the three objective functions: minimizing the total cost, the net rejected items and the inverse total value of purchasing (TVP), while satisfying capacity and demand requirement constraints. Design/methodology/approach: The model is established for supplier selection problem and later the proposed single objective model is used to calculate the optimum order quantities among the selected suppliers. A numerical example is given to illustrate how the model is applied. Findings: In this article, we proposed a single objective function to solve the fuzzy multi-item multi-objective model in order to calculate the optimum order quantities to each supplier. Practical implications: Single objective function, which is able to consider the relative importance of the goals, is proposed to solve the model. A numerical example is given to illustrate how the model is applied. Originality/value: This approach is able to help the DM evaluate the suppliers in order to find out the appropriate order to each them, and allows purchasing manager(s) to manage supply chain performance on service, cost, quality and etc. the suppliers’ price breaks, which depend on the sizes of order quantities, affects the selection process.